Spatiotemporal Trends of Colorectal Cancer Mortality Due to Low Physical Activity and High Body Mass Index From 1990 to 2019: A Global, Regional and National Analysis - Man, Jinyu; Zhang, Tongchao; Yin, Xiaolin; Chen, Hui; Zhang, Yuan; Zhang, Xuening; Chen, Jiaqi; Yang, Xiaorong; Lu, Ming (Frontiers in Medicine, 2022)
Background: Understanding the spatiotemporal trends of colorectal cancer (CRC) deaths caused by low physical activity (LPA) and high body mass index (BMI) is essential for the prevention and control of CRC. We assessed patterns of LPA and high BMI-induced CRC deaths from 1990 to 2019 at global, regional, and national levels. Methods: Data on CRC deaths due to LPA and high BMI was downloaded from the Global Burden of Disease 2019 Study. We calculated estimated annual percentage change (EAPC) to quantify spatiotemporal trends in the CRC age-standardized mortality rate (ASMR) due to LPA and high BMI. Results: In 2019, CRC deaths due to LPA and high BMI were estimated as 58.66 thousand and 85.88 thousand, and the corresponding ASMRs were 0.77/100,000 and 1.07/100,000, with EAPCs of−0.39 [95% confidence interval (CI):−0.49,−0.29] and 0.64[95% CI: 0.57, 0.71] from 1990 to 2019 respectively. Since 1990, the ASMR of CRC attributable to LPA and high BMI has been on the rise in many geographic regions, especially in low middle and middle sociodemographic index (SDI) regions. Thirteen countries had a significant downward trend in CRC ASMR attributed to LPA, with EAPCs < −1. And, only 4 countries had a significant downward trend in CRC ASMR attributable to high BMI, with EAPCs < −1. Countries with a higher baseline burden in 1990 and a higher SDI in 2019 had a faster decline in ASMR due to high BMI and LPA. Conclusions: The burden of CRC caused by LPA and high BMI is on the rise in many countries. Countries should adopt a series of measures to control the local prevalence of obesity and LPA in order to reduce disease burden, including CRC.